THE INFLUENCE OF DIGITALIZATION ON BANKING FINANCIAL INSTITUTIONS IN INDONESIA - Destri Ayu Larasati Mahayana; I Wayan Novy Purwanto (Transpublika Publisher, 2023)
The development of digitalization systems has a direct impact on the banking industry, both positively and negatively. This research aims to examine the influence of digitalization on financial banking institutions in Indonesia and how efforts are made to prevent the negative effects of banking service digitalization in Indonesia. This study employs a normative legal research method, utilizing a legislative approach. One of the positive impacts of digitalization on financial banking institutions in Indonesia is the emergence of digital banking services. However, one of its negative consequences is the potential for cybercrimes. To prevent the negative effects of banking service digitalization in Indonesia, various preventive measures can be taken, such as not disclosing PINs to others and exercising caution when using internet applications. Additionally, the Financial Services Authority (OJK) has issued Regulation No. 13/POJK.03/2020 amending Regulation No. 38/POJK.03/2016 regarding the Implementation of Risk Management in the Use of Information Technology by Commercial Banks.